2018
DOI: 10.1007/s41669-018-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Acromegaly Treatment in Brazil: A Budget Impact Analysis of Pituitary Surgery Compared with Long-Term Octreotide LAR

Abstract: Background Acromegaly is a rare, chronic and debilitating disease whose treatment places a high burden on health systems. In the reality of the Brazilian public health network, many patients are kept on drug treatment because of barriers to access to surgery. Objective The aim of this study was to estimate the costs and budget impact of routine transsphenoidal endoscopic surgery in relation to those of long-term drug treatment with octreotide long-acting release (LAR) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Considering the exceptionality conferred by the pandemic, telemedicine became the only accessible option to maintain adequate medical assistance. That being said, the adherence in the study group was similar to that observed in face-to-face consultations carried out in previous years [13][14][15] and the medical effectiveness of the remote medical assistance seemed to be comparable to the conventional protocol in our service.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Considering the exceptionality conferred by the pandemic, telemedicine became the only accessible option to maintain adequate medical assistance. That being said, the adherence in the study group was similar to that observed in face-to-face consultations carried out in previous years [13][14][15] and the medical effectiveness of the remote medical assistance seemed to be comparable to the conventional protocol in our service.…”
Section: Discussionsupporting
confidence: 82%
“…The estimated high costs of pharmacological therapy demand a robust social protection system to prevent inequity in access to medicines. 13 To have access to a supply of drugs, the patient needs to accomplish several steps: (1) have a medical evaluation; (2) obtain the printed prescription; (3) take it to the central highcost public pharmacy; and (4) receive the medicine and bring it back to the hospital to receive the injection.…”
Section: Local Policies and Economic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to this is whether these LoC patterns differ from that of the general population. Studying utilization of LoC is essential for efficient resource allocation and healthcare funding, [20,21], especially as the costs of treating acromegaly can A c c e p t e d M a n u s c r i p t be exorbitant. [22] The main objective of this analysis was to evaluate the likelihood, number, and cost of healthcare services used, according to LoC, by individuals with acromegaly and a matched control group.…”
Section: Introductionmentioning
confidence: 99%